Interaction of University Students and Their Parents as a Factor of Minimizing Educational Risks - N. V. Shabrova (Высшее образование в России)
The article presents the results of a study of the features of interaction between students and their parents as a factor of minimizing the educational risks. These features are analyzed through the prism of the functions of their interaction, such as economic, emotional, parental control. The empirical basis of the article comprises the data of sociological surveys conducted in the Sverdlovsk region in 2018 and 2021. The methodical strategy was based on a combination of quantitative (mass survey of students (n=953) and parents (n=452)) and qualitative (focus groups with university students (n=7) and in-depth interviews with parents of university students (n=20)) methods of collecting information. The analysis revealed changes in the interactions of students and their parents, mainly related to the transformation of the nature, form of education and activity of students. It is shown that the implementation of the functions of interaction between students and their parents allows minimizing the risks of non-compliance of the chosen specialty with the needs and interests of students, reducing educational, professional motivation, poor-quality vocational training at university.